Pengaruh Komitmen Organisasi, Karakteristik Pekerjaan Terhadap Kepuasan Kerja Karyawan dan Motivasi Kerja Sebagai Variabel Intervening - Dina Prasetyaningrum (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2020)
Background – Employee job satisfaction becomes a matter that must be considered for the success and success of the company. There are factors that can affect job satisfaction, namely factors in workers and work factors including organizational commitment, job characteristics, and work motivation. Aim – This study aims to determine and analyze partially and simultaneously the effect of organizational commitment, job characteristics, and work motivation on job satisfaction of employees of PT. Pertamina RU IV (Persero) Cilacap. Design / methodology / approach – The research method uses quantitative by using path analysis techniques (Path Analysis). Samples were taken by purposive sampling technique with a total sample of 123 people, which included Maintenance Execution employees of PT. Pertamina RU IV (Persero) Cilacap. Findings – The results of the study indicate that job satisfaction is positively and significantly affected by organizational commitment through intervening variables of work motivation; job characteristics; and work motivation. Research implication – The results of the study can be used as a company reference in paying attention to organizational commitment, job characteristics, work motivation, and job satisfaction to achieve organizational goals that are effective and efficient. Limitations – Limitations of this study on the number of variables used to predict job satisfaction are limited simultaneously at 66.4%, so that it can use other variables that can provide a greater influence on job satisfaction.